Effect of Seed Priming on Cucurbita pepo Germination under Drought Stress - Kazem Badeleh (پژوهش‌های بذر ایران, 2015)
To evaluate the effect of priming on seed germination of Cucurbita pepo in drought stress conditions, a factorial experiment was conducted as completely randomized design with three replications. Treatments included drought stress at five levels of osmotic potential (zero, 0.3, 0.6, 0.9 and 1.2 MP), priming at levels of GA3 (250 ppm to 24 hours), KNO3 (0.2% for 24 hours) Hydro prime (H2O) (to 24 hours) and control. The results showed that priming effect was significant on germination percentage, germination rate, mean daily germination, the average time required for germination and germination rate index. A significant difference was found between drought stress on seed germination rate. In addition, the interaction of seed priming and drought stress was significant on all traits (germination percentage, germination rate, average daily germination, the average time required for germination, germination rate daily, the coefficient of germination rate and the seed vigor). Seed priming, particularly in severe drought stress levels, led to significant increase in mean germination percentage, germination rate and seed vigor. Furthermore, the results of our study indicated that Cucurbita pepo seed priming had partial resistance to drought. Gibberellin acid in the first grade and the hydro priming in second grade can improve the germination and growth of the seedlings under drought stress.